Evaluation of the sealing ability of bone cement as furcation perforation repair material when compared with mineral trioxide aggregate and calcium phosphate cement: An in-vitro study - Rashmi Chordiya; Hemalatha Hiremath; Sandeep Metgud; Anant Heda (Wolters Kluwer Medknow Publications, 2010)
Aim: This study was undertaken to compare the sealing ability of bone cement as furcation perforation repair material when compared with mineral trioxide aggregate and calcium phosphate cement. Materials and Methods: A total of 70 sound mandibular molars were selected for this study. The sample teeth were randomly divided into five groups: group I - n=20, perforation repair material used, mineral trioxide aggregate; group II - n=20, perforation repair material used, calcium phosphate cement; group III - n=20, perforation repair material used, bone cement; group IV - positive control, n=5, the furcation were not repaired with any material; group V - negative control, n=5, furcation area intact, no perforation done. The teeth were immersed in silver nitrate solution for 2 hours and then rinsed with photographic developer solution for 6 hours. They were then sectioned in a longitudinal direction and examined under a stereomicroscope. In each section the actual values of dye leakage were calculated from outer margins of perforation to the level of pulpal floor and were then subjected to statistical analysis. Results: An unpaired 't' test revealed that different groups exhibited significantly different dye penetrations (P<0.01). Conclusion: Furcation perforation repaired with MTA showed minimum microleakage (mean 54.5%), calcium phosphate cement showed maximum microleakage (100%), and bone cement showed moderate dye leakage (87.8%).